Modeling Groundwater-Soil-Plant-Atmosphere Exchanges in Fractured Porous Media - Ireson, Andrew M.; van der Kamp, Garth; Nachshon, Uri; Butler, Adrian P. (Procedia environmental sciences, 2013)
Models for the soil-plant-atmosphere system, especially large scale models, frequently ignore interactions with underlying groundwater, and ignore fractures or macropores which may strongly influence the system response. Unsaturated fractured porous media can exhibit a range of behavior, depending on both the characteristics of the porous matrix and the fractures, and the climatic conditions to which they are subject. A dominant characteristic in surficial fractured porous geological formations is the vertical distribution of fractures in the near surface region. This paper explores how these different modes of behavior operate at various field sites and under different climatic conditions. Two diverse fractured porous settings are considered: fractured glacial till of the semi-arid, seasonally frozen Canadian prairies and the Chalk in humid, temperate south east England. Interpretations from hypothetical hillslope scale model simulations provide insights into how the properties of the material, and in particular the distribution of the fractures and the matrix hydraulic conductivity, affect the spatial distribution of evapotranspiration and the timing, magnitude and spatial distribution of groundwater recharge. Such behavior is not captured in conventional large scale models which consider only a shallow, one-dimensional soil moisture balance.